1994
DOI: 10.1002/j.1460-2075.1994.tb06280.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the [4Fe-4S]-cluster converting iron regulatory factor from its RNA-binding form to cytoplasmic aconitase.

Abstract: The control of cellular iron homeostasis involves the coordinate post-transcriptional regulation of ferritin mRNA translation and transferrin receptor mRNA stability. These regulatory events are mediated by a soluble cytoplasmic protein, iron regulatory factor (1U), which binds specifically to mRNA hairpin structures, termed iron-responsive elements (IREs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
153
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(163 citation statements)
references
References 50 publications
8
153
1
1
Order By: Relevance
“…Molecular-weight markers are in lane 1 (numbers correspond to molecular weights in kDa). IRP1 C437S/C503S retained IRE-binding activity (not shown), as expected from previous studies (Philpott et al, 1994;Hirling et al, 1994). Importantly, IRP1 C437S/C503S did not show the heterogeneous behavior displayed by wild-type IRP1.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Molecular-weight markers are in lane 1 (numbers correspond to molecular weights in kDa). IRP1 C437S/C503S retained IRE-binding activity (not shown), as expected from previous studies (Philpott et al, 1994;Hirling et al, 1994). Importantly, IRP1 C437S/C503S did not show the heterogeneous behavior displayed by wild-type IRP1.…”
Section: Resultssupporting
confidence: 89%
“…Firstly, the fact that IRE binding itself is so markedly affected by the presence or absence of the Fe-S cluster while the cluster ligands are not involved in IRE binding # 2006 International Union of Crystallography All rights reserved argues strongly for a conformation-driven switch (Philpott et al, 1994;Hirling et al, 1994). Secondly, the apo form of IRP1 is much more protease-sensitive than the holo form (Swenson & Walden, 1994;Schalinske et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The metazoan IRE-BP (or iron regulatory factor, IRF) is a phylogenetically conserved bifunctional protein: When it contains a [4Fe-4S] cluster, it functions as a cytosolic aconitase; in the absence of the metals, it binds the IRE RNA (Hirling et al 1994). Its size (90 kD) has precluded NMR studies, and there is no crystal structure of the protein with or without RNA.…”
Section: Introductionmentioning
confidence: 99%
“…It is presumed to be structurally homologous to the mitochondrial aconitase (mAcn), which does not bind RNA (Robbins and Stout 1989). The binding site for RNA was modeled in the cleft of the two domains (Basilion et al 1994;Hirling et al 1994;Kaldy et al 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Western blot analysis of PMR-1 following estrogen stimulation+ Ten microgram samples of hepatocyte protein isolated at the indicated times following estrogen stimulation were analyzed by Western blot using a polyclonal antiserum to PMR-1+ Lane 1 is a standard of 1 ng of purified PMR-1+ A parallel blot of 100 ng of hepatocyte protein per lane was probed with sheep antiserum to vitellogenin as a control for estrogen stimulation+ ern blot in Figure 1 provide suggestive evidence that, like hMPO, PMR-1 is made as a larger precursor and is proteolytically processed to the form identified on polysomes+ It may or may not be a coincidence that the site of this putative processing event occurs at a position similar to that which separates the propeptide and light chain of hMPO+ Expression of the full-length PMR-1 cDNA in a recombinant baculovirus (Fig+ 4) yielded the 80-kDa protein (PMR80) expected from the sequence, but this was not processed to the 60-kDa form isolated from liver polysomes and lacked enzymatic activity+ These data indicate both that Sf9 cells lack the enzymatic pathway by which PMR-1 is proteolytically processed, and that processing is required to generate a catalytically active form of the enzyme+ In contrast, the recombinant 60-kDa form of PMR-1 estimated to represent the protein isolated from polysomes (PMR60) is an active endonuclease (Figs+ 5-7)+ PMR-1 was originally identified by its ability to generate a doublet cleavage product from a portion of the 59 end of albumin mRNA (Pastori et al+, 1991b)+ This was later mapped to consensus overlapping APyrUGA elements in a singlestranded loop region (Chernokalskaya et al+, 1997)+ That study also demonstrated that the purified enzyme also cleaved albumin mRNA at a number of sites that did not correspond to this consensus sequence+ Recombinant PMR60 did not cleave albumin mRNA at consensus APyrUGA elements (Fig+ 7)+ However, the recombinant enzyme generated much the same pattern of nonconsensus cleavages as the purified enzyme, indicating both that it is an endonuclease and that it is indeed PMR-1+ The reason recombinant PMR60 does not cleave at APyrUGA elements is not known, although we suspect it is related to folding of the protein, because a similar result was obtained with purified PMR-1 that was renatured after treatment under denaturing conditions (data not shown)+ It is unclear how a putative messenger RNase evolved from the peroxidase gene family+ Myeloperoxidase lacks detectable ribonuclease activity (Fig+ 2C), indicating this family of proteins does not have a secondary enzymatic function+ Perhaps some insight into this may be found in the dual function of several metabolic enzymes as RNA-binding proteins+ IRP-1 functions as a regulator of iron metabolism through its role in the translational repression of ferritin mRNA (Gray & Hentze, 1994) and stabilization of transferrin receptor mRNA (Binder et al+, 1994)+ Iron binding to the active site of this protein converts IRP1 from its RNA-binding form to cytoplasmic aconitase (Hirling et al+, 1994)+ Glyceraldehyde-3-phosphosphate dehydrogenase is a well-characterized hydrolytic enzyme which can bind AU-rich RNA sequence elements through its NAD(ϩ) binding site (Nagy & Rigby, 1995)+ Glutamate dehydrogenase was identified as the protein whose binding to the 39 UTR of cytochrome c oxidase mRNA correlates with liver-specific mRNA stabilization (Preiss et al+, 1995), and AUH, an ARE-binding protein, has enol...…”
Section: Estrogen Induces Only a Moderate Increase In Pmr-1mentioning
confidence: 99%